(untitled) (Zaporizhzhia Historical Review, 2021)
The article is devoted to the looks of the Ukrainian political elite of period of Hetmanshina in relation to saving of political, territorial and etnocultural unity of Ukrainian earths. Keywords: cathedral, state institutions, hetman government, political integrity, cossacks elite, military-political patronage.